Engineering chemistry : theory and practicals - Chatterjee, Nivedita (U.N.Dhar & Sons, 2018)
Engineering chemistry : theory and practicals / Chatterjee, Nivedita. -- Kolkata: U.N.Dhar & Sons, 2018 540 Ac176 No. of Copies : 2